Hubungan Gizi Ibu, Pola Asuh Anak Balita, dan Status Ekonomi Rumah Tangga terhadap Stunting: Studi Kasus di Dusun Arjowinangun dan Dusun Mergosono, Kota Malang - Saputri, Lorenza Arinda; Sulistyorini, Anita; Novianti, Vivi; Kurniawan, Agung (Universitas Airlangga, 2025)
Background: Indonesia has a higher potential to experience an increase in stunting cases, because around 31% of children under the age of five experience stunting. The prevalence can be influenced by direct and indirect factors, from pregnancy to early childhood growth. The increasing number of stunting cases affects the quality of human resources, resulting in various significant impacts, such as declining public health, economic stagnation, poverty, and social inequality. Objectives: This study aimed to examine the correlation between maternal nutrition, toddler feeding patterns, and household economic status with stunted cases in Kelurahan (Urban Village of) Arjowinangun and Kelurahan Mergosono, Malang City. Methods: This study employed a quantitative approach, utilizing a retrospective cross-sectional design with correlation analysis methods. As many as 60 respondents (mothers and stunted toddlers) participated in the study. Statistical analysis includes Spearman’s Rank test for bivariate analysis with a 95% significance level (p=0.05) and multiple logistic regression for multivariate analysis. Results: Bivariate analysis revealed significant positive correlations between maternal nutrition (p=0.000), toddler feeding patterns (p=0.000), and household economic status (p=0.000) with stunted cases. Among these variables, household economic status demonstrated the strongest correlation, with a correlation coefficient of 0.617. Multivariate analysis showed that the household economic status variable had a greater chance of correlating with stunted cases by 30.989 times. Conclusion: All three independent variables were significantly correlated with stunted, with household economic status being the strongest determinant.